1997
DOI: 10.1097/00042560-199705010-00010
|View full text |Cite
|
Sign up to set email alerts
|

T Cells From Individuals in Advanced Stages of HIV-1 Infection Do Not Proliferate but Express Activation Antigens in Response to HIV-1-Specific Antigens

Abstract: Like T cells from healthy subjects, those of HIV-1-infected patients are capable of expressing activation antigens on their surface after antigenic or mitogenic stimulation, but their proliferative activity is strongly reduced or even absent, especially in patients with advanced stages of the disease. The characteristic of expressing activation antigens in response to different stimuli in the absence of cell proliferation is shared by CD4+ and CD8+ T-cell subsets from HIV-1-infected patients. The number of T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Recently, similar results were obtained in a cohort of HIV-1 infected intravenous drug abusers in advanced stages of the disease [7]. PHA-stimulated T-cells from these patients showed expression levels of the activation antigens CD25 and CD71 that were similar to those seen in healthy adult controls; however, in contrast to the controls, T-cells from patients showed a reduced proliferation rate in vitro.…”
Section: Discussionsupporting
confidence: 73%
“…Recently, similar results were obtained in a cohort of HIV-1 infected intravenous drug abusers in advanced stages of the disease [7]. PHA-stimulated T-cells from these patients showed expression levels of the activation antigens CD25 and CD71 that were similar to those seen in healthy adult controls; however, in contrast to the controls, T-cells from patients showed a reduced proliferation rate in vitro.…”
Section: Discussionsupporting
confidence: 73%
“…On the other hand, our results show a significant decrease in the proportion of CD4 þ T cells producing IL-2 in HIV þ symptomatics versus asymptomatics, and an inverse correlation between percentage IL-2 þ CD4 þ T cells and RNA viral load, suggesting that the defect in IL-2 production is progressive. It would therefore be interesting to investigate the mitogen-induced production of IL-2 from proliferating and nonproliferating CD4 þ T cells using flow cytometry, since this may have relevance to the impaired antigen-specific immune responses in activated T helper cells from HIV-infected patients [20]. A number of non-cytopathic viruses encode proteins which can interfere with anti-viral host immunity and thus modulate the immune response in favour of maintaining a chronic viral persistence in the host [21].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, subjects were able to mount responses against cytomegalovirus, herpes simplex virus, and PHA. Defects in HIV-1specific lymphocyte proliferative responses prior to the loss of recall, allogeneic, and mitogen antigen responses in HIV-1infected individuals have now been described in numerous clinical studies (2,5,14,16). Recently, it has been shown that HIV-1-specific lymphocytes responses to p24 antigen could be augmented in subjects on antiviral therapy prior to seroconversion (16).…”
Section: Discussionmentioning
confidence: 99%